Being an Inspiring Teacher in Realizing Competitive Education in the Era of Society 5.0 - Ijudin, Ijudin; Ainissyifa, Hilda; Wakila, Yasya Fauzan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This research discusses about being an inspiring teacher. This research focuses on the description of conceptions and steps that must be taken by teachers in the learning process, in relation to students to create active teaching and learning. The source of this research data was obtained from several sources in the form of supporting and accompanying references in accordance with the research theme. This research is library research using a qualitative approach, which is trying to describe a variable, symptom or situation. The results of this paper show that teachers must always have and develop the quality of personality competencies with the aim of creating an active learning process and providing inspirational meaning. From the conception of being an inspirational teacher, it will give birth to a teacher's skills in learning and competence that prioritizes psychologically moral and attachment, not only oriented to the knowledge and skills of students such as inspiring active learning, teacher writing activities, teachers and happiness, as well as teachers and students change.